Copper uptake and subcellular distribution in five marine phytoplankton species - Zhang, Peng; Liu, Yang; Zhang, Li (Frontiers in Marine Science, 2022)
Copper (Cu) uptake and trophic transfer in marine plankton at the environmentally relevant levels have rarely been investigated. In this study, we investigated the Cu uptake and subcellular distribution in five phytoplankton (Isochrysis zhanjiangensis, Phaeocystis sp., Isochrysis galbana, Chaetoceros sp. and Phaeodactylum tricornutum) belonging to two taxa Chrysophyta and Bacillariophyta, and the following trophic transfer to rotifer Brachionus plicatilis by using stable isotope tracing method. In 2-hour exposure, Cu uptake rates were 20.8–60.3 amol h-1 cell-1 (amol = 10-18 mol) in the phytoplankton exposure to 4.82 × 10-13 mol L-1 free Cu activity ([Cu2+]). Cu uptake rates were increased with the increase of [Cu2+] in all the phytoplankton species. Generally, Cu uptake rate constants (kus) were lower in Bacillariophyta (Chaetoceros sp. and P. tricornutum) than Chrysophyta (I. zhanjiangensis, Phaeocystis sp. and I. galbana). While in long-term (6 day) exposure, more Cu was accumulated in the Bacillariophyta than in Chrysophyta, suggesting Bacillariophyta might have more Cu capacity than Chrysophyta. Size effects of cells on Cu uptake were not observed among these five phytoplankton. Cu was mainly distributed in the heat-denatured protein plus organelle fraction and head-stable protein fraction in all the five phytoplankton. The Cu assimilation efficiencies (AEs) in rotifer feeding I. zhanjiangensis, Phaeocystis sp., I. galbana, Chaetoceros sp. and P. tricornutum were 63.4%, 57.6%, 60.2%, 77.4% and 14.6%, respectively. These Cu AEs were positively correlated to the Cu distribution in the trophically available metal fraction (TAM) in different phytoplankton. These results herein demonstrated that different marine phytoplankton had different strategies to accumulate Cu that influence Cu transfer to the predators. Therefore, the variation of the phytoplankton community will change the Cu biogeochemistry in marine environment.